Perfil proteico e análise da atividade enzimática no plasma seminal de catetos (pecari tajacu linnaeus, 1758) - Santos, Erika Aparecida Araújo dos (2013)
The main mechanisms involved in fertility of male include post-translational modifications as well as the presence or absence of certain proteins in seminal plasma. Furthermore, some enzymes are important to protect the sperm cells against damage caused by reactive oxygen species (ROS). The seminal proteins can be evaluated by laboratory for additional information about the reproductive potential of animals evaluated. Thus, the molecular studies of seminal plasma are important to uncover the mechanisms and molecules which are essential for the conservation of semen quality. Therefore, two studies were directed to describe important components of seminal plasma of peccaries (Pecari tajacu LINNAEUS, 1758). Initially, we conducted the classic seminal analysis of motility, vigor, functional and structural integrity of the sperm membrane and sperm morphology. As a result, we verified that all animals were healthy and sexually mature. The first study aimed to define the seminal plasma proteins, then proteomics seminal plasma was evaluated by two-dimensional electrophoresis and proteins were identified by mass spectrometry (LC - MS / MS). As a result, we identified 93 spots on bidimensional gel, corresponding to 23 different proteins, from which the PSP-1 was found in abundance. This protein plays a role of chaperone for other proteins incorrectly folded and it is essential in seminal plasma. The second study verified the existence of activity of catalase, superoxide dismutase, guaiacol peroxidase and ascorbate peroxidase in seminal plasma. The enzyme activity was analyzed by the spectrophotometry. As a result, no activity was detected for any enzyme. It is suggestive that other compensatory mechanisms protect the cells against ROS, for example, the significant presence of glutathione peroxidase (GPx) founded in the seminal plasma of peccaries. Both studies contributed for the increasing the information about the reproductive physiology of the peccaries and then the use of reproductive biotechnologies in this species